We (believe or distrust) the people: o controle de constitucionalidade das Emendas à Constituição e o problema da autoridade - Ana Luisa de Navarro Moreira (2014)
What is the moral justification for attributing to the people the authority to make constitutional changes? Why is it so important that the people deliberate and participate in the discursive construction of political decisions? In this Dissertation, it is assumed that the only way to vindicate the law’s claim to legitimate authority is by recognizing its democratic character. Democracy provides the sole moral justification for legal authority and legal obligation. On the basis of Habermas’ discursive conception of democracy, I will attempt to demonstrate that the normative ideal of citizenship, which recognizes that the people are simultaneously authors and recipients of the laws that govern them, exerts an important influence on a theory of legal authority. The legitimacy of the authority comes from the people, so that is the people who legitimize the authority of the government, the law and the Constitution. By the same token, it should be the people who provide legitimacy to constitutional change through amendment procedures. When the court adjudicates on the validity of a constitutional amendment it interferes in a decisive way in a constitutional decision on whether or not a constitutional change will produce effects in a given community, and, thereby, provide a new basis for the constituent project that was initiated in the enactment of the Constitution. It is our object of inquiry in this Dissertation the judicial review of constitutional amendments, in which a judicial decision may invalidate a legislative decision to amend the Constitution despite the deep moral disagreement about the abstract moral principles therein. The heart of the debate about the legitimacy of the authority of judicial review comprises two correlated questions which will be faced by this Dissertation: what the constitution means and who decides what it means. In the end, I intend to show that the Brazilian Federal Supreme Court lacks moral and legal authority to pronounce the material unconstitutionality of Amendments to the Brazilian Constitution, at least while they are pronounced in the light of deep moral disagreement. On the contrary, in this special form of strong judicial review, the Court must act as a public reasoner that helps the community to enhance the quality of the democratic decisions, in order to contribute to its rationality by providing solid arguments of principle. The entitlement of the decision-power, however, must remain with the people, who shall exert it either directly of by their representatives, inasmuch as they are the source of legitimate authority. The ground of the authority of the constitution and of the decision that revises a constitutional admendment, therefore, lies in the construction of a discursive process of justification of legal norms that provides to the people the power to decide by themselves.